A RADIOCARBON DATE FROM EARLY DYNASTIC KISH AND THE STRATIGRAPHY AND CHRONOLOGY OF THE YWN SOUNDING AT TELL INGHARRA. Issue 1 (5th January 2016) - Zaina, Federico
Abstract : Between 1927 and 1930 a joint expedition by the University of Oxford and the Field Museum of Chicago to the site of Kish opened a series of soundings (ZY, Y, YW and YWN) on the mound of Tell Ingharra in order to investigate the earliest periods of the settlement. This paper presents a detailed analysis of the YWN sounding utilizing previously unpublished documentation and excavated objects, and offers a new interpretation of the evidence. In addition, a new radiocarbon date assigns the latest phase from the sounding to the ED IIIb to Akkadian transition and it can be compared usefully with existing dates from several central and north Mesopotamian sites.